Prevention of parent to child transmission of HIV: where are we? a decade’s analysis - Donthamsetty, Manoj; E. S., Siddharth; Mruthyunjaya, S.; Banapurmath, C. R. (International Journal of Contemporary Pediatrics, 2018)
Background: Vertical transmission of HIV remains the main source of pediatric HIV infection with transmission rates as high as 25%-45% without intervention. This rate can be reduced to levels below 2% with effective interventions. Methods: This study summarizes the interventions taken up by the PPTCT centre from 2003 to 2014. The interventions were based on WHO guidelines adopted by NACO. All HIV positive mothers who were followed up or referred to sisu raksha-PPTCT centre were included in the study and their infants were followed up till 18 months of age. All the HIV positive mothers were given appropriate counselling and CD4 count estimation was done. They were given antiretroviral drugs as per respective WHO guidelines adopted by NACO and were counselled regarding feeding option. The babies were given antiretroviral drugs as per guidelines and were followed up for a period of 18 months after birth. Results: From 2003 to 2010, the rate of mother to child transmission was 5.2% (30/573). From 2011 to 2014, after implementation of WHO 2010 guidelines, the transmission rate reduced to 3.5% (12/342). Further analysis of the data was done. From 2003 to 2010, 72.6% (441/607) mothers practiced exclusive breastfeeding. From 2011 and 2014, 95.5% (345/361) mothers practiced exclusive breastfeeding. Conclusions: Effective implementation of WHO PPTCT guidelines, early diagnosis in pregnancy, antiretroviral drug intake in mother and Nevirapine prophylaxis to the baby together reduce mother to child transmission of HIV considerably.